High-resolution measurements of sediment fluxes, turbidity, and bed-level changes using SediMeter and sediment traps in Admiral Marina, Port Dickson, Malaysia (October 25–31, 2011, configuration 1) - Lin, Chin Yik; Lam, Su Shiung; Er, Jenn Wei; Lee, Wah Sza; Jia Hui, Ang; Erlingsson, Ulf; Gan, Yew Sun; Yee, Woei Shyan (In: Lin, CY et al. (2025): Utilizing optical backscatter sensor and sediment traps for measuring sediment dynamics in low energy marine environment [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984064, 2025)
This dataset contains sediment fluxes, sedimentation rates, turbidity levels, and bed elevation data collected from SediMeter (SM) and Sediment Trap (ST) instruments deployed at Admiral Marina, Port Dickson, Malaysia. Measurements were performed to quantify sediment dynamics within a low-energy marina environment. The SM units used infrared sensors emitting 945 nm pulses to detect turbidity (in Formazin Backscatter Units - FBU) and bed-level changes at high temporal resolution. The first deployment occurred from October 25 to 31, 2011, with turbidity measurements averaging 554.08 ± 174.14 FBU, indicating active sediment deposition processes. This deployment aimed to evaluate short-term sedimentary events, influenced by local hydrodynamics such as tidal variations and wave actions. Instruments were installed via scuba diving on soft-bottom substrates with minimal anthropogenic disturbances. This dataset supports studies on sediment resuspension, erosion, and accumulation in semi-enclosed marinas (Lin et al., 2025).
Keywords: marina; sedimentation rate; sediment fluxes; Sediment trap; SediMeter; turbidity